Vagus Nerve Stimulation Attenuates Multiple Organ Dysfunction in Resuscitated Porcine Progressive Sepsis - Kohoutova, Michaela; Horak, Jan; Jarkovska, Dagmar; Martinkova, Vendula; Tegl, Vaclav; Nalos, Lukas; Vistejnova, Lucie; Benes, Jan; Sviglerova, Jitka; Kuncova, Jitka; Matejovic, Martin; Stengl, Milan (Critical care medicine, 2019)
OBJECTIVES: To investigate the potential benefits of vagus nerve stimulation in a clinically-relevant large animal model of progressive sepsis. DESIGN: Prospective, controlled, randomized trial. SETTING: University animal research laboratory. SUBJECTS: Twenty-five domestic pigs were divided into three groups: 1) sepsis group (eight pigs), 2) sepsis + vagus nerve stimulation group (nine pigs), and 3) control sham group (eight pigs). INTERVENTIONS: Sepsis was induced by cultivated autologous feces inoculation in anesthetized, mechanically ventilated, and surgically instrumented pigs and followed for 24 hours. Electrical stimulation of the cervical vagus nerve was initiated 6 hours after the induction of peritonitis and maintained throughout the experiment. MEASUREMENTS AND MAIN RESULTS: Measurements of hemodynamics, electrocardiography, biochemistry, blood gases, cytokines, and blood cells were collected at baseline (just before peritonitis induction) and at the end of the in vivo experiment (24 hr after peritonitis induction). Subsequent in vitro analyses addressed cardiac contractility and calcium handling in isolated tissues and myocytes and analyzed mitochondrial function by ultrasensitive oxygraphy. Vagus nerve stimulation partially or completely prevented the development of hyperlactatemia, hyperdynamic circulation, cellular myocardial depression, shift in sympathovagal balance toward sympathetic dominance, and cardiac mitochondrial dysfunction, and reduced the number of activated monocytes. Sequential Organ Failure Assessment scores and vasopressor requirements significantly decreased after vagus nerve stimulation. CONCLUSIONS: In a clinically-relevant large animal model of progressive sepsis, vagus nerve stimulation was associated with a number of beneficial effects that resulted in significantly attenuated multiple organ dysfunction and reduced vasopressor and fluid resuscitation requirements. This suggests that vagus nerve stimulation might provide a significant therapeutic potential that warrants further thorough investigation.
Keywords: Vagus Nerve; zvířata; Hemodynamics; srdeční mitochondrie; Prospective Studies; myokard; prospektivní studie; hemodynamika; mužské pohlaví; Multiple Organ Failure; prasata; srdce; Hyperlactatemia; Myocardium; nervus vagus; náhodné rozdělení; elektrostimulační terapie; Mitochondria, Heart; Monocytes; vazokonstriktory; Electric Stimulation Therapy; Heart; progrese nemoci; Sepsis; multiorgánové selhání; Animals; počet leukocytů; Female; hyperlaktatemie; Disease Progression; Random Allocation; Swine; modely nemocí na zvířatech; sepse; Organ Dysfunction Scores; vyhodnocení orgánové dysfunkce; ženské pohlaví; Leukocyte Count; Male; Vasoconstrictor Agents; Disease Models, Animal; monocyty